Time series analysis of non-invasive hemodynamic monitoring data in neonates with hypoxic-ischemic encephalopathy - Balog, Vera; Vatai, Barbara; Kovacs, Kata; Szabo, Attila J.; Szabo, Miklos; Jermendy, Agnes (Frontiers in Pediatrics, 2023)
Background and aims: Hemodynamic instability is common in neonates with hypoxic-ischemic encephalopathy (HIE) undergoing therapeutic hypothermia (TH). Rewarming is a critical period and non-invasive circulatory monitoring may be helpful in guiding cardiovascular supportive therapy. The aim of the study was to provide a comprehensive analysis of cardiac function parameters during TH and its relation to neurodevelopmental outcome. Methods: In a prospective, observational study, 26 neonates with moderate-severe HIE were enrolled, born between 2016-2019. A hemodynamic monitor based on electrical velocimetry (ICON, Osypka Medical GmbH, Berlin, Germany) was used. Heart rate (HR), stroke volume (SV), cardiac output (CO) data was recorded continuously throughout TH and rewarming. Neurological outcome was assessed at 2 years of age using the Bayley Scales of Infant Development II. scale. Favorable outcome was defined as >70 points on both the psychomotor and mental scale. Time-series analysis was used and features of cardiac function were described to perform logistic regression modeling for outcome prediction. Results: Fourteen (54%) patients had favorable and 12 (46%) had adverse outcome. Data collection started from median [IQR] of 11.8 [7.0; 24.3] hours (h) of life and lasted until 84.0. [81.8; 87.0] h. During TH, the mean HR of the favorable outcome group was significantly lower than that of the adverse outcome group (86 ± 13 / min vs. 104 ± 18 / min, p=0.01). During rewarming HR increased similarly in both groups. SV was unaffected by rewarming, and showed a slowly increasing trend. SV of the favorable outcome group was significantly higher compared to the adverse outcome group (1.55 ± 0.23 mL/kg vs 1.29 ± 0.30 mL/kg, p= 0.035). In line with this, CO was similar in both groups (136 ± 27 mL/kg/min vs 134 ± 36 mL/kg/min), and a significant 25% increase in CO was observed during rewarming. Based on multiple regression modeling, HR during TH was independently associated neurological outcome (p=0.023). Conclusion: Based on continuous hemodynamic monitoring, patients with adverse outcome have lower SV and higher HR to achieve similar CO to patients with favorable outcome during TH. HR during hypothermia is independently associated with the neurodevelopmental outcome.